Dei Verbum, and the Interpretation of Sacred Scripture. - SCOLLO, GIUSEPPE G. (Logos: A Journal of Catholic Thought & Culture)
The article examines Pope Joseph Ratzinger's pivotal role in the Second Vatican Council's document Dei Verbum, highlighting his contribution to a hermeneutic of Scripture that integrates divine inspiration and human understanding. Topics include Ratzinger's early academic formation and teaching, his influence on biblical interpretation and the lasting impact of his theological work on the Church's understanding of faith and Scripture.